Efficacy and safety of autologous peripheral blood stem cell transplantation for Philadelphia chromosome-positive acute lymphoblastic leukemia: A study protocol for a multicenter exploratory prospective study (Auto-Ph17 study). Issue 52 (December 2017) - Nishiwaki, Satoshi; Sugiura, Isamu; Miyata, Yasuhiko; Saito, Shigeki; Sawa, Masashi; Nishida, Tetsuya; Miyamura, Koichi; Kuwatsuka, Yachiyo; Kohno, Akio; Yuge, Masaaki; Kasai, Masanobu; Iida, Hiroatsu; et al.
Abstract: Introduction: The prognosis of Philadelphia chromosome positive acute lymphoblastic leukemia (Ph + ALL) has been dramatically improved since the introduction of tyrosine kinase inhibitors (TKIs). Although allogeneic hematopoietic cell transplantation (allo-HCT) is a major treatment option, the role of autologous peripheral blood stem cell transplantation (auto-PBSCT) has been reconsidered, especially in patients who achieved early molecular remission. Methods and analysis: This is a multicenter exploratory study for Ph + ALL patients aged between 55 and 70 years who achieved complete molecular remission within 3 cycles of chemotherapy. The target sample size is 5, and the registration period is 2 years. The primary endpoint is Day100- mortality after transplantation, and the secondary endpoints are survival, relapse rate, nonrelapse mortality, and adverse events. This study is divided into 3 phases: peripheral blood stem cell harvest, transplantation, and maintenance. Chemomobilization is performed using a combination of cyclophosphamide (CPM), doxorubicin, vincristine (VCR), and prednisolone (PSL). As a preparative regimen, the LEED regimen is used, which consists of melphalan, CPM, etoposide, and dexamethasone. Twelve cycles of maintenance therapy using a combination of VCR, PSL, and dasatinib are performed. In association with relapse, the minimal residual disease (MRD) of BCR-ABL chimeric gene and T-cell subsets are analyzed both before and after auto-PBSCT. Ethics and dissemination: The protocol was approved by the institutional review board of Nagoya University Hospital and all the participating hospitals. Written informed consent was obtained from all patients before registration, in accordance with the Declaration of Helsinki. Results of the study will be disseminated via publications in peer-reviewed journals. Trial registration: Trial registration number UMIN000026445.